2012
DOI: 10.1192/bjp.bp.111.100594
|View full text |Cite
|
Sign up to set email alerts
|

White matter abnormalities and illness severity in major depressive disorder

Abstract: Widespread alterations in white matter integrity are evident in major depressive disorder. These abnormalities are heightened with increasing severity of depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
72
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(96 citation statements)
references
References 69 publications
20
72
2
1
Order By: Relevance
“…Similar to the studies in Table 1, the subsample analyses showing FA differences varied considerably in which regions were identified. Interestingly, a region consistently identified as showing FA differences between MDD patients and controls in our post-hoc analysis was the genu of the corpus callosum-a region identified in the previously published reports (Cole et al, 2012;Korgaonkar et al, 2011). Given with the well-known prefrontal distortion in DTI images, it is possible that this region is especially vulnerable to false positive findings in DTI analyses (Wu et al, 2008).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Similar to the studies in Table 1, the subsample analyses showing FA differences varied considerably in which regions were identified. Interestingly, a region consistently identified as showing FA differences between MDD patients and controls in our post-hoc analysis was the genu of the corpus callosum-a region identified in the previously published reports (Cole et al, 2012;Korgaonkar et al, 2011). Given with the well-known prefrontal distortion in DTI images, it is possible that this region is especially vulnerable to false positive findings in DTI analyses (Wu et al, 2008).…”
Section: Discussionmentioning
confidence: 87%
“…In an effort to better understand the pathophysiology of MDD and develop more effective treatments, much research has focused on delineating the structure and function of this mood regulation network. Although many studies have focused on the function of the network (Drevets et al, 2008b;Hafeman et al, 2012;Mayberg, 2003a, b;Murray et al, 2011;Phillips, 2006), including functional connectivity between key brain regions (Craddock et al, , 2012Greicius, 2008Greicius, , 2007James et al, 2009;Seminowicz et al, 2004;Sheline et al, 2010), others have focused on the structural connectivity of the network, ie, the white matter (WM) pathways between brain regions (Abe et al, 2010;Blood et al, 2010;Cole et al, 2012;Cullen et al, 2010;Kieseppa et al, 2010;Korgaonkar et al, 2011;Ma et al, 2007;Tha et al, 2013;Wu et al, 2011;Zhu et al, 2011;Zou et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with normal controls, WM integrity can differ not only in patients with major depression, but also in those with subclinical depression [33][34][35][36][37]. These WM integrity changes may be involved in the aetiology of depression symptoms not only in major depressive disorders, but also in other psychiatric disorders that contain a depressive component in their symptomatology.…”
Section: Discussionmentioning
confidence: 90%
“…The results of meta-regression analysis showed that there was no significant association between white matter microstructure alterations and relevant socio demographic and clinical variables. The results, however, should be interpreted with some caution in consideration of the small sample size in the present study and the limited variability in the data, since some studies investigating white matter abnormalities in patients with MDD have provided evidence that decreased FA in the SLF and CC were associated with the depressive symptoms 14,39,44,[64][65][66] and negatively cor related with depression severity 28,65,67,68 and illness duration. 14,28 Moreover, patient characteristics of the included studies were heterogeneous, which may result in the negative results.…”
Section: Discussionmentioning
confidence: 93%